UiTM Green Centre workshop series 2 - UiTM, UGC (UiTM Green Centre, 2025)
UiTM Green Centre has organized Workshop series 2 related to UI Green Matric World Ranking and a related ranking workshop at UiTM Hotel. At this workshop, there has also been a briefing session of assessment related to University sustainability by UiTM Global (UG). This cooperation is important to ensure the cohesive energy of all parties to ensure the UiTM ranking in the world is always a level to be proud of.